Neonatal congenital hyperinsulinism in Indonesia - I.Made Arimbawa; I.Wayan Eka Satriawibawa; Kadek Deddy Ariyanta; I.Made Darmajaya; Pande Putu Yuli Anandasari; Luh Putu Iin Indrayani Maker (Elsevier, 2021)
Introduction: Congenital hyperinsulinism (CHI) is resulted from dysregulated insulin secretion from hyperplastic and hyperactive but apparently normally structured β-cells islet. Principal management is maintaining normal blood glucose level by giving high GIR and pharmacological therapy. Surgery is chosen when CHI is unresponsive to pharmacological treatment. Case: A 3-days-old girl was admitted to Sanglah Hospital, with a complaint of lethargic, refused to drink, seizure, weak tonus. The patient had a very low blood glucose level, normal lactate level, normal blood pH, high fasting insulin and C-Peptide level, normal cortisol, normal growth hormone, normal TSHs, and FT4 level, no ketonuria, no glucosuria, and no proteinuria. An abdominal CT scan showed diffuse dilatation of the caput, corpus, and tail of the pancreas without pancreatic duct dilatation. The patient was treated with Hydrocortisone, Octreotide, Nifedipine, and a high glucose infusion rate. The patient was undergone subtotal pancreatectomy and only remained 22% from the previous size. Histopathologic examination revealed serous acini zymogenic cells that were arranged in lobules, hyperplastic of the Langerhans islands, and cell within Langerhans islands. Post-surgery condition, she had controlled blood glucose, good drink tolerance, without a recurrent seizure. Conclusion: CHI is a rare disease and differential diagnosis of persistent hypoglycemia in the infant. Comprehensive and multidisciplinary management is required for a better outcome.